Map showing the overland and overseas flights of Charles A. Lindbergh / designed by Ernest Clegg - Clegg, Ernest (New York : John Day Co., 1928)
Covers from Norway west to Alaska and from Brazil north to Greenland.; Includes index, text, and col. ill.; Accompanied by storage folder, constructed of paper, 32 x 38 cm.; Fold-lined. Color; 1:13,000,000